Executed Women Haunt, Inspire Iranian Baha'is 40 Years Later. - Agence France-Presse (VOA News, 2023)
One by one, the 10 women, mostly aged under 30, went defiantly to their deaths by hanging in a city square in Shiraz in southern Iran. The youngest was only 17 years old.
Keywords: 2023-06 June